1987
DOI: 10.1073/pnas.84.3.794
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive transforming genes in x-ray-transformed mammalian cells.

Abstract: DNAs from hamster embryo cells and mouse C3H/lOT1/2 cells transformed in vitro by x-irradiation into malignant cells transmit the radiation transformation phenotype by producing transformed colonies (transfectants) in two mouse recipient lines, the NIH 3T3 and C3H/101/2 cells, and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

1988
1988
1999
1999

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(38 citation statements)
references
References 38 publications
3
35
0
Order By: Relevance
“…This model uses chemically initiated neoplastic hamster embryo cells as an alternative in vitro system the characteristics of which make it relevant for studies of the cellular and molecular biology of human carcinogenesis (DiPaolo et al, 1969a(DiPaolo et al, ,b, 1971(DiPaolo et al, , 1986. The treatment of Syrian hamster cells in vitro with chemical or physical carcinogens has been used as the experimental model in other laboratories, and proved to be e cient for the detection of non-ras transforming genes (Borek et al, 1987;Gilmer et al, 1988). We demonstrated that ras activation is a low frequency event in this system (Notario et al, 1990), and established the participation of oncogenes and tumor suppressor genes in the carcinogenesis process (Notario et al, 1990;Albor et al, 1994a,b).…”
Section: Introductionmentioning
confidence: 99%
“…This model uses chemically initiated neoplastic hamster embryo cells as an alternative in vitro system the characteristics of which make it relevant for studies of the cellular and molecular biology of human carcinogenesis (DiPaolo et al, 1969a(DiPaolo et al, ,b, 1971(DiPaolo et al, , 1986. The treatment of Syrian hamster cells in vitro with chemical or physical carcinogens has been used as the experimental model in other laboratories, and proved to be e cient for the detection of non-ras transforming genes (Borek et al, 1987;Gilmer et al, 1988). We demonstrated that ras activation is a low frequency event in this system (Notario et al, 1990), and established the participation of oncogenes and tumor suppressor genes in the carcinogenesis process (Notario et al, 1990;Albor et al, 1994a,b).…”
Section: Introductionmentioning
confidence: 99%
“…However, the presence of a mutated c-ras gene has not been demonstrated so far (Sawey et al, 1988). Borek et al (1987) have demonstrated the presence of a unique non-ras transforming gene in cell lines derived from irradiated hamster embryo cells and mouse C3H 10 T1/2 cells. This work was supported by a grant from the Medical Research Council.…”
mentioning
confidence: 99%
“…Other oncogenes must also be involved in the development of non-small-cell lung cancers. DNA from cells transformed in vitro by X-rays (28,29) (30)(31)(32)(33)(34)(35)(36)(37), with the exception of squamous cell carcinomas (38,39). Mutations in this gene are also infrequent in murine lung tumors (40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%